2014
DOI: 10.13005/ojc/300449
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of Ag nanoparticles and loading it on activated carbon as a novel adsorbent for removing methyl orange by using surface response methodology

Abstract: After synthesizing Ag nanoparticles and loading onto activated carbon (from olive stone), the adsorption of methyl orange (MO) onto the prepared nanoparticles was studied. In this connection, the effect of experimental parameters such as pH range, reagent concentration, contact time, dosage amount of adsorbent and so on, on the adsorption process were studied. The experimental results were analyzed upon various kinetic models such as pseudo first order reaction, pseudo second order reaction, Elovich model, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Silver nanoparticles doped activated carbon (Ag NPs/AC) is a functional material with various application mainly in adsorption and antibacterial activity. Previous work proven the effectiveness of Ag NPs/AC in removing dye and water pollutants such as phosphate [10], crystal violet [3,12], malachite green [13,14], methyl orange [15,16] and methylene blue [14,17] with no study in removing RB dye. Silver nanoparticles (Ag NPs) can enhance the active sites of activated carbon (AC) for better adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles doped activated carbon (Ag NPs/AC) is a functional material with various application mainly in adsorption and antibacterial activity. Previous work proven the effectiveness of Ag NPs/AC in removing dye and water pollutants such as phosphate [10], crystal violet [3,12], malachite green [13,14], methyl orange [15,16] and methylene blue [14,17] with no study in removing RB dye. Silver nanoparticles (Ag NPs) can enhance the active sites of activated carbon (AC) for better adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The common methods used to remove industrial dyes are electro-coagulation, carbon sorption, redox treatment, flocculation, UV photo-degradation 18 . Reports have shown that metallic nanoparticles can act as photocatalytic agents [19][20][21] . Therefore, in the study we were investigated photocatalytic activity of synthesized Ag NPs using B. multifida extract on MB dye.…”
Section: Introductionmentioning
confidence: 99%